Implementation of the Principle of Freedom of Contract in Making Musyarakah and Ijarah Deeds Made by Notaries at Bank Muamalat Kendari Branch - Saharia, Siti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The profit sharing portion is still regulated by Bank Muamalat Kendari Branch, even though in the provisions there are profit and loss sharing or revenue sharing methods are by mutual agreement. This is certainly contrary to the sharia principle, namely gharar which is uncertainty or not in accordance with the initial agreement. This results in carrying out business activities that are contrary to sharia principles being an act that is prohibited for Islamic Commercial Banks and Islamic Financing Banks. The formulation of the problem in this study is how is the application of the principle of freedom of contract in making musyarakah and ijarah at Bank Muamalat Kendari Branch? and how is the strength of the evidence of musyarakah and ijarah deeds made before a Notary? The aim of this research is to determine the application of the principle of freedom of contract in the profit sharing system in musyarakah and ijarah financing contracts at Bank Muamalat Kendari Branch and to find out and analyze the strength of proof of musyarakah and ijarah deeds made before a Notary Public.